2017
DOI: 10.1038/s41598-017-01133-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide fitness analyses of the foodborne pathogen Campylobacter jejuni in in vitro and in vivo models

Abstract: Campylobacter is the most common cause of foodborne bacterial illness worldwide. Faecal contamination of meat, especially chicken, during processing represents a key route of transmission to humans. There is a lack of insight into the mechanisms driving C. jejuni growth and survival within hosts and the environment. Here, we report a detailed analysis of C. jejuni fitness across models reflecting stages in its life cycle. Transposon (Tn) gene-inactivation libraries were generated in three C. jejuni strains and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 88 publications
(116 reference statements)
1
59
0
Order By: Relevance
“…Of the 98 mutations conferring increased in vitro fitness by DEseq2, validation experiments confirmed only 3 out of the 5 tested mutations (60%) ( Fig 2B ), revealing a slightly higher proportion of false-positive results with genes in this category. In general, false-positive results are not uncommon with Tn-seq screens [ 58 , 64 , 76 ] and may reflect a variety of reasons. The initial Tn-seq screen is a complex competitive environment involving thousands of mutants whereas validation studies tend to compare only a single mutant to the WT pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 98 mutations conferring increased in vitro fitness by DEseq2, validation experiments confirmed only 3 out of the 5 tested mutations (60%) ( Fig 2B ), revealing a slightly higher proportion of false-positive results with genes in this category. In general, false-positive results are not uncommon with Tn-seq screens [ 58 , 64 , 76 ] and may reflect a variety of reasons. The initial Tn-seq screen is a complex competitive environment involving thousands of mutants whereas validation studies tend to compare only a single mutant to the WT pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…This result highlights that the 4 h in vitro library expansion step in our in vivo Tn-seq screen setting likely introduces some bias into our in vivo fitness datasets. Mutant pool expansion following in vivo Tn-seq screens, by mutant pool plating on agar [ 65 , 76 , 77 ] or culture in broth [ 64 , 78 ], is often required when library DNA extraction directly from tissue represents a limiting step to the Tn-seq procedure. This extra step is particularly important when using the Mme I-based Tn-seq approach [ 72 ], as it requires high quality DNA (no shearing).…”
Section: Discussionmentioning
confidence: 99%
“…jejuni M1 adapts rapidly to introduction into a water environment, instigating gene expression changes that allow it to adapt to the stressful conditions, whilst maintaining viability. A recent complementary study by de Vries et al (2017) used Transposon Directed Insertion Sequencing (TRADIS) to identify genes essential for survival in vitro and in vivo [ 94 ]. Although comparing knockout studies to whole-transcriptome studies is difficult because gene knockouts will likely produce different transcriptional profiles due to deregulation or disruption of genetic pathways, in both studies a gene involved in the oxidative stress response: trxC , was identified as a key candidate gene for survival in model water systems.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the role of CapC in C. jejuni, isogenic mutants of capC were constructed in C. jejuni 81116 and C. jejuni M1 by insertion of a chloramphenicol resistance cassette. We were unable to complement the capC mutants, as we were unable to clone the capC coding sequence into the pC46 or pSV009 complementation vector in the correct orientation, despite repeated attempts (36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%